Heterometal‐Embedded Organic Conjugate Frameworks from Alternating Monomeric Iron and Cobalt Metalloporphyrins and Their Application in Design of Porous Carbon Catalysts. (27th April 2015) - Lin, Qipu; Bu, Xianhui; Kong, Aiguo; Mao, Chengyu; Bu, Fei; Feng, Pingyun
<x xml:space="preserve">Abstract</x> The use of an alternately conjugated networking method to prepare the first porous heterometalloporphyrinic frameworks with ordered alternation of Fe and Co moieties is presented. Subsequent carbonization gives an Fe and Co co‐embedded porous carbon composite with a very high activity and remarkable electrochemical stability for oxygen reduction reaction in both alkaline and acidic electrolytes.